ANALISIS FILOSOFIS TENTANG PETA KONSEPTUAL PENELITIAN HUKUM NORMATIF DAN PENELITIAN HUKUM SOSIOLOGIS - Zulfadli Barus (Jurnal Dinamika Hukum, 2013)
Research is done by someone if there is any problem, a situation which reflects contradiction between the ideal fact and the real one. The elements which create the problem could be found by doing research. There are two kinds of research conceptual map in   law. They are: The rational-consistence-interpretative and the empirical-objective constructive. Legal research is based on rational-consistence-interpretative and socio-legal research is based on empirical-objective-constructive. These models are based on different concepts. The elements of legal research   are: rationalism, legal positivism, coherence theory, a priori, analysis, deduction, consistency, interpretative, library research, secondary data and qualitative. The elements of socio-legal research are empiricism, historical jurisprudence, correspondence theory, a posteriori, objectivity, constructive, synthesis, induction, field research, primary data and quantitative.Keywords: conceptual map, legal research, socio legal research